Manajemen Penanggulangan Bencana Kebakaran Hutan dan Lahan oleh Kantor Penanggulangan Bencana Daerah (KPBD) di Kabupaten Indragiri Hulu - Amalia Luthfiah Hananti; Sujianto Sujianto (Politeknik Kampar, 2025)
Indragiri Hulu Regency is one of the districts in Riau Province which is the most extensive district for forest and land fires in 2024. There are problems, namely the lack of human resources who have disaster competence, the lack of training for the task force, the lack of dissemination of disaster-prone information, facilities and infrastructure that are not enough. The purpose of this study was to determine how the management of forest and land fire disaster management carried out by the Regional Disaster Management Office (KPBD) of Indragiri Hulu Regency and to find out the obstacles faced. This research uses disaster management theory proposed by Neil Grig which consists of planning, organizing, leadership, coordinating, controlling, supervising, budgeting, finance. This research uses descriptive qualitative research methods, and data obtained through interviews, observation, and documentation. From the results of this study, it can be seen that the management of forest and land fire disaster management carried out by the Regional Disaster Management Office (KPBD) of Indragiri Hulu Regency is quite good, but there are obstacles such as a fairly limited budget, limited facilities and infrastructure that are quite adequate, the difficulty of the terrain, and the lack of awareness of the community in disaster management of forest and land fires in Indragiri Hulu Regency.